RELEVANCE OF STATUS NEEDS FOR ENCOURAGING CUSTOMERS RESPONSE: A STUDY FROM RETAILER’S PERSPECTIVES - Gomes, Judith; Gain, Namrata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores relative importance of status of small retailers in organized era. It measures the degree to which status needs related factors were related to customer response according to retailers. The model was tested with data collected from a retailer survey. Data was analysed using descriptive statistics, factor and correlation analysis. In general, results of research support framework proposed for reference. Status needs was positively driven by response needed with requirement. Shopping enjoyment exhibited that merchandise management can help to build customer response towards the store and in customer records, personal information and loyalty points can also encourage customer towards their store. Contrary to other items they responded are not much related to encourage customers. A further important finding is a different but significative item store ambience can be also worth encouraging customers to the store. This concludes if they manage merchandises and maintain records with appropriate store ambience can generate customer response.